2012
DOI: 10.1136/emermed-2011-200482
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of adverse drug event recognition by emergency physicians in a French teaching hospital

Abstract: ADEs are frequent in EDs and are not well recognised by emergency physicians, especially when the drug is involved in a multifactorial pathological condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
44
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 24 publications
10
44
1
1
Order By: Relevance
“…), they are generally not inappropriate in this subset. Roulet et al (2013) estimated the frequency and the severity of drug-related visits in ED, in order to assess ADE recognition by emergency physicians (October 2007-31 March 2008. In their prospective cross-sectional single centre study in France, a total of 95 out of 423 eligible patients experienced an ADE.…”
Section: Discussionmentioning
confidence: 99%
“…), they are generally not inappropriate in this subset. Roulet et al (2013) estimated the frequency and the severity of drug-related visits in ED, in order to assess ADE recognition by emergency physicians (October 2007-31 March 2008. In their prospective cross-sectional single centre study in France, a total of 95 out of 423 eligible patients experienced an ADE.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many studies conducted in EDs have been limited to one hospital centre [13,14], a specific population [15,16], specific therapeutic classes or type of ADEs [17][18][19][20]. Other findings are attributable to retrospective study design [21,22], short periods of observation [2,5,6,[23][24][25], or lack of information on preventability [7,10,26]. Moreover, some literature studies reported preventability assessment referred only to therapeutic classes [4,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of ED visits associated with ADRs have been limited to one hospital setting, 14 16 a specific population, 17 21 specific classes of drug 22 , 23 or types of ADRs, 24 , 25 a retrospective study design, 26 , 27 short periods of observation, 13 , 28 32 or did not provide information on preventability. 33 35 More extensive studies of ED visits for outpatient ADRs are thus crucial and needed. We have determined the prevalence, preventability, seriousness requiring hospitalization, subsequent 30-day mortality, and economic impact of ADRs presenting to multiple EDs serving a large proportion of the Lombardy region over a 2-year period.…”
Section: Introductionmentioning
confidence: 99%